A Development of Khim Teaching Module for Informal Education System - Chinsarojana, Lada; Charanyananda, Anak (Journal of Fine and Applied Arts Khon Kaen University, 2020)
The purpose of this qualitative research was to develop a Khim teaching module for an informal education system and to find its efficiency in a qualitative way. The researcher invited 6 adult research participants aged between 21-65 years old to do private music lessons according to Khim teaching module design. The Khim teaching module has been developed and already passed the qualitative evaluation by 3 Thai music educators. The lessons in the teaching module included 4 private periods for 1 hour each. After the students had finished all the lessons, the researcher determined the teaching module’s efficiency from the student’s accomplishment and student development observation record which were assessed individually by 5 different music educators. The results revealed that all students were able to pass the researcher’s criteria in Khim playing and performing posture, short and long tone playing, duration, rhythm, fluency, and accuracy in performing the entire piece. Thus, all students were able to obviously developed themselves at a satisfactory level.